COMPARISON OF PM2.5 AND PM10 IN URBAN AND SUBURBAN BANDUNG AND LEMBANG AREAS - Noorsalam, Hadi
Bandung and Lembang are areas that represent urban and suburban areas. It is known that in the urban ares the concentration values of PM2.5 and PM10 are higher than the suburban area Santoso (2008). However, differences in the concentration of pollutants in Lembang and Bandung have only been studied based on sources of pollutants. While the meteorological parameters rainfall also influence Tiwari (2012). Therefore, a comparative study of PM2.5 and PM10 was carried out in the urban and suburban areas of Bandung and Lembang using meteorological factors. Data processing is conducted by correlation method to analyze the effect of rainfall, temperature and wind factors on PM2.5 and PM10 concentration values in the urban and suburban areas. Based on the results rainfall and wind factors affected the concentration of PM2.5 and PM10 in the urban and suburban areas. While the effect of temperature can only be seen in the Bandung area. Rainfall affects changes in the difference in PM2.5 concentration values between Bandung and Lembang by 4.87 ?g/m3 and changes in the difference in PM10 concentration values are 11.49 ?g/m3. The high value of wind speed at the DJF has an effect on the value of the low pollutant concentration for the month.